2015
DOI: 10.1039/c4ra13474e
|View full text |Cite
|
Sign up to set email alerts
|

Flying-seed-like liquid crystals. Part 4: a novel series of bulky substituents inducing mesomorphism instead of using long alkyl chains

Abstract: We have synthesized a novel series of flying-seed-like derivatives (3a~g) based on phthalocyaninato copper(II) (abbreviated as PcCu) substituted by bulky groups {PhO (a), Thus, we have revealed that mesomorphism could be induced by these novel bulky substituents instead of using long alkyl chains, and that the mesophase structures were greatly affected by the number and position of methoxy groups. Especially, it is very interesting that the derivatives having methoxy group(s) at the meta position(s), 3c, 3e, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0
5

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 24 publications
1
21
0
5
Order By: Relevance
“…Therefore, presence of the methoxy group may be a key point on the homeotropic alignment. We have previously reported that a novel type of flying-seed-like liquid crystals show mesomorphism despite absence of long chains [36][37][38][39][40][41]. For example, (m-CH 3 OPhO) 8 PcCu (8) in Fig.…”
Section: Homeotropic Alignment Depending On the Presence Of The Methomentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, presence of the methoxy group may be a key point on the homeotropic alignment. We have previously reported that a novel type of flying-seed-like liquid crystals show mesomorphism despite absence of long chains [36][37][38][39][40][41]. For example, (m-CH 3 OPhO) 8 PcCu (8) in Fig.…”
Section: Homeotropic Alignment Depending On the Presence Of The Methomentioning
confidence: 99%
“…8[A] shows mesomorphism. The mesomorphism of flying-seed-like liquid crystals is originated from the free rotation or flip-flop of bulky substituents, e.g., m-CH 3 OPhO groups [39]. Therefore, the o-CH 3 OPhO (VAN) group in (C 14 S) 6 PcCu-VAN-C 60 (3b) may also enhance the mesomorphism and homeotropic alignment.…”
Section: Homeotropic Alignment Depending On the Presence Of The Methomentioning
confidence: 99%
“…Мезофаза соединения 1а существует в достаточно широком интервале температур, равном 87 °С (табл. 2), что характерно для «flying-seeds-like» мезогенов [13,14].…”
Section: результаты и обсуждениеunclassified
“…В настоящее время интерес ученых вызывают мезогенные соединения с заместителями типа «flying-seeds-like» (семян-«крылаток»), особенностью которых является отсутствие протяженных алкильных заместителей [13,14] и чрезвычайно широкий интервал существования мезофазы. Среди таких соединений -тетразамещенные фталоцианины с фрагментами 4-кумилфенола (4-(1-метил-1-фенилэтил)фенола).…”
Section: Introductionunclassified
“…[1,4,17,18] It was later shown that the presence of aliphatic substituents was not absolutely necessary for the formation of columnar mesophases. [19] The so-called flying-seeds-like compounds (FSLM) synthesized by Ohta et al, [20][21][22][23][24] unlike classical discotic mesogens, did not contain extended aliphatic substituents in the molecule. Nevertheless, the mesophase was formed due to the filling of free volumes at the periphery of the columns with mobile aromatic substituents.…”
Section: Introductionmentioning
confidence: 99%